Flexible strain sensors based on epoxy/graphene composite film with long molecular weight curing agents. Issue 35 (2nd May 2019) - Meng, Qingshi; Zhao, Yu; Liu, Zhiwen; Han, Sensen; Lu, Shaowei; Liu, Tianqing
ABSTRACT: Flexible strain sensors based on epoxy/graphene composite film with long molecular weight curing agents have critical roles in the development of advanced polymer composite films that combine mechanical robustness with functional properties such as electrical conductivity for many applications. In this experiment, flexible epoxy/GnP composite film is obtained by using flexible curing agent J2000. A percolation threshold of electrical conductivity was observed at merely 0.97 vol% GnPs, and the composite electrical conductivity increased to 10 −6 S/cm at 5.0 vol %. The composite films were mechanically strong enough to be used as a flexible strain sensor. Our sensor can clearly detect the stretching of the forearm skin caused by a fist pulse and back of hand movement and achieve an enhancement of the resistance signal of up to 50%. When the GnPs content reaches 5%, Young's modulus and tensile strength increase to 21 MPa and 1.3 MPa, respectively. © 2019 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2019, 136, 47906. Abstract :